Pengaruh Kesehatan Mental Terhadap Resiliensi Dan Problem Solving Remaja di SMK Negeri 3 Kota Bengkulu - Bela Anggraini, Fiki; Andriansyah, Habi; Yolanda Pracella, Aisha (Yayasan Darussalam Bengkulu, 2023)
This article aims to look at the influence of mental health on the resilience and problem solving of teenagers at SMKN 3 Bengkulu City. The subjects of this research were 108 students at SMKN 3 Bengkulu City. Sampling used the Cluster Sampling technique and data collection by distributing questionnaires directly. The research results show that the R squere of 0.163 (16.3%) is an influence where 16.3% of mental health does not influence resilience and problem solving at SMKN 3 Bengkulu City, the remaining 8.37% is influenced by other variables that are not included in this research.